Pengabdian Kepada Masyarakat Mengenai Cara Hidup Hemat & Cerdas Finansial Ala Gen-z - Sofinatun Najah; Dewinta Amanda Salim; Dara Umaedi; Prasetyo Nugroho (CV. Multi Kreasi Media, 2026)
Community service is one of the manifestations of the Tri Dharma of Higher Education which channels the needs of the community with academic competence. Pamulang University through the Accounting Study Program in collaboration with the Pondok Serut Residents Hall partner carried out a Community Service (PKM) activity on May 10, 2026 which aims to increase public understanding, especially the younger generation, regarding how to implement a proper frugal lifestyle and smart financial management in the digital era. The material presented in this activity raised a theme entitled